Evaluating the Relationship of Visceral Adiposity Index with Different Metabolic Phenotypes and Cardiovascular Markers in Non-Diabetic Subjects - Monica I Cardona-Alvarado; Gabriela Lopez-Moreno; Herlinda Aguilar-Zavala; Nicte FigueroaVega; Elva Perez-Luque (Medical Science: Trends and Innovations Vol. 9, 2025)
Background: The visceral adiposity index (VAI) is a gender-specific mathematical model, which originates from observation in a healthy normal/overweight population of a linear relationship between body mass index (BMI) and waist circumference (WC). VAI provides information of visceral adipose tissue function and insulin sensitivity. Aim: This study aims to evaluate the relationship of VAI with different metabolic phenotypes and cardio metabolic risk markers in non-diabetic subjects. Methods: A total of 183 health clinical subjects from 30 to 50 years of age, with normal weight and with obesity grade I were recruited. Anthropometric measures were taken and quantified glucose, lipids, insulin, high-sensitivity C-reactive protein (hs-CRP) and adiponectin concentrations. Unhealthy phenotype was defined according to the criteria; Visceral Adiposity index (VAI) was calculated. To analyze the differences between VAI quartiles and the metabolic variable, one-way ANOVA and post-hoc test were used. Furthermore, a multiple regression analysis was conducted to evaluate the association between VAI with insulin levels, the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) and glucose, adjusted by sex and BMI. Results: In the study group, four groups were found according to their metabolic state, which includes MHNO (metabolically healthy non-obesity), MUNO (Metabolically unhealthy non-obese subject), MUO (metabolically unhealthy obese subject) and MHO (metabolically healthy obese). Among others, 40% were MHO, they showed lower serum glucose, triglycerides, insulin, hs-CRP levels, systolic and diastolic blood pressure, HOMA-IR than MUO. Metabolically unhealthy non-obese subjects (MUNO) showed higher serum triglycerides, insulin levels, HOMA-IR than the metabolically healthy non-obesity (MHNO) subjects. MUNO and MUO subjects had higher VAI values than MHNO and MHO subjects. In a logistic regression analysis using the cut-offs of VAI quartile 4, >2.25 in women and >1.86 in men found a strong association with glucose, HOMA-IR and adiponectin concentrations. In ROC analysis using these cut-off determined for glucose concentrations >100 mg/dL, an area under the curve of 0.83 in men and 0.71 in women; for HOMA-IR 0.78 only in men, and for adiponectin 0.69 in men and 0.91 in women. Conclusion: VAI estimates visceral fat distribution, and it is a useful determinant of the phenotype change and substituted the necessity to take high-cost imaging studies, thereby making the prediction much more practical in daily clinical practice and population studies for the assessment of cardiometabolic risk associated with visceral obesity. Therefore, VAI is a useful indicator to evaluate the metabolic risk both of non-obese and obese individuals.